2016
DOI: 10.1371/journal.pone.0154227
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Estimated Prevalence of Endometriosis and Adenomyosis in Northeast Italy: A Data Linkage Study

Abstract: Despite being quite frequent and having serious implications in terms of symptomatology and fertility, data on incidence and prevalence of endometriosis and adenomyosis following gold standard definitions are dramatically lacking. The average time from onset of symptoms to diagnosis in industrialized countries still ranges from five to ten years. Using the regional centralized data linkage system, we calculated incidence and prevalence of endometriosis and adenomyosis in the female population of Friuli Venezia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
88
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 26 publications
14
88
1
6
Order By: Relevance
“…An Icelandic study with both visually verified and histologically confirmed diagnosis, during 1981-2000, reported an incidence of 0.1% (3). A similar figure of 0.14% of surgically verified endometriosis was also reported in an Italian study performed in the early 2010s, and showed a decreasing trend in the incidence (6). Thus, introduction of the laparoscopic surgery might have also increased the incidence of the procedures (2).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…An Icelandic study with both visually verified and histologically confirmed diagnosis, during 1981-2000, reported an incidence of 0.1% (3). A similar figure of 0.14% of surgically verified endometriosis was also reported in an Italian study performed in the early 2010s, and showed a decreasing trend in the incidence (6). Thus, introduction of the laparoscopic surgery might have also increased the incidence of the procedures (2).…”
Section: Discussionsupporting
confidence: 78%
“…In our study the age-standardized incidence rates of the first surgically verified endometriosis diagnosis was 0.12%, being at its highest in 1987 and decreasing to 0.04% in 2012, even though more than 80% of the procedures have lately been performed via laparoscopy. The decreasing incidence is in contrast to many previous studies (3,4), but in agreement with the recent Italian study (6). Among patients who entered to our cohort during the first decade, there may be those with previous operations.…”
Section: Discussionmentioning
confidence: 99%
“…In a German population, the highest prevalence rate was observed among women aged 35–44 years (12.8 per 1000), similar to our age‐specific estimate. The average incidence rate of 72 per 100 000 in our study is comparable with that of other published database studies in the UK, Iceland, and Italy (range 97–112 per 100 000 population), as well as Sweden (77 per 100 000 person‐years) . Still, the true prevalence and incidence of endometriosis in real‐world settings is not sufficiently established.…”
Section: Discussionsupporting
confidence: 62%
“…In a rare population-based study, the estimated prevalence of adenomyosis in Northeast Italy is reported to be 0.18%, much lower than that of endometriosis (1.14%) [17]. The age-specific incidence of adenomyosis is very different from that of endometriosis, reaching its peak at the age interval of 46-50 years [17]. These numbers seem to be low, possibly because the cases were all histologically confirmed.…”
Section: Epidemiologymentioning
confidence: 92%
“…This wide variability stems from variations in the histological criteria adopted for diagnosis and the techniques used to procure myometrial samples [15]. In a rare population-based study, the estimated prevalence of adenomyosis in Northeast Italy is reported to be 0.18%, much lower than that of endometriosis (1.14%) [17]. The age-specific incidence of adenomyosis is very different from that of endometriosis, reaching its peak at the age interval of 46-50 years [17].…”
Section: Epidemiologymentioning
confidence: 99%